If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + -1k = 36 Solving 90 + -1k = 36 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-90' to each side of the equation. 90 + -90 + -1k = 36 + -90 Combine like terms: 90 + -90 = 0 0 + -1k = 36 + -90 -1k = 36 + -90 Combine like terms: 36 + -90 = -54 -1k = -54 Divide each side by '-1'. k = 54 Simplifying k = 54
| -1-4s=8 | | 110+(3x-8)+(3x+6)=180 | | 5(3n+34)+8(n+1)= | | 20/j=10 | | 25x^2+4y^2=10 | | 10x-12=8x-11 | | 3x^2=-17x+28 | | 7-p=34 | | 3=t/8-3 | | 600/(0.1)(8) | | 16-2x=0 | | -2x^2y^3(3x^2y+5x-6y+2)= | | (-56)(-90)= | | 8=20-4h | | 12x=3+2x+1 | | 6+7t=34 | | -62=9-62 | | 2(x+3)=88 | | 52=8b-36 | | -40=8x+8 | | 2.2(-4r-9)+0.6r= | | 29-w=18 | | -15+10(x)=95 | | 120/21 | | 9ex=107 | | 3(8n+32)+5(n+1)= | | 19x+28=5x-23+14x | | 10r=40 | | 15/20-14/20 | | 7/1.75 | | 6x-(4x+2y)+12= | | 1/4x+5=1/2x-7 |